First Grade English Reader - Zúñiga, Roberto (Nicaragua: TERRA NUOVA and CIDCA, 1992)
English text for the first grade of primary school, contains images and illustrations.
Col. Educ
Keywords: 1. ENGLISH 2. ENGLISH READER 3. LINGUISTICS 4. EDUCATION